Investidores do mercado financeiro: investigação da impulsividade e da autorregulação na tomada de decisão e do estresse percebido gerado em operações financeiras - Crispim, Ingrid Aparecida Siqueira (2022)
Psychological characteristics such as emotions, fear and greed can influence financial operations. Thus, the lack of attention in an operation can cause serious losses in Market operations. This emotional distress is among the threats that influence investor behavior. This research aimed to investigate factors that influence the decision-making process in financial operations. In order to measure and obtain these data, the following instruments were used: Perceived Stress Scale – PSS-14; Barratt Impulsivity Scale - BIS-11; Short Self-Regulation Questionnaire – QRAR; Investor Profile Analysis (API) and Sociodemographic Questionnaire. The sample consisted of 156 participants, the collection was carried out online and, based on the results, they were organized into three groups: Conservative Investor (G1-IC), Moderate Investor (G2-IM) and Bold Investor (G3-IA). A questionnaire was applied to a convenience sample of professional investors who work in the financial and capital markets. In the procedure, all the collection, correction and analysis of the results referring to the instruments of cognitive and personality measurement was carried out by a qualified professional in Psychology. SmartPLS 3.0M3 was used for structural equation modeling analysis, and SPSS (Version 23.0 for Windows, IBM, São Paulo, SP, Brazil) was used for demographic data analysis. The results of this survey can be useful to Financial and Capital Market Operators, when consistent with controlling the feeling of loss. The lack of emotional and behavioral control reflects in the decision-making process. Impulsive choice and impulsive action have negative effects on the financial result. Therefore, the investor in the moment of euphoria, in a volatile market, can make impulsive choices and impulsive decisions. It is concluded when a financial market operator acts impulsively, many decisions are being influenced by emotions. When influenced by emotions, they make mistakes for not controlling themselves, individuals need to know themselves and develop emotional skills consistent in financial choices.(AU)